2020
DOI: 10.1002/cne.24952
|View full text |Cite
|
Sign up to set email alerts
|

LacZ‐reporter mapping ofDlx5/6expression and genoarchitectural analysis of the postnatal mouse prethalamus

Abstract: We present here a thorough and complete analysis of mouse P0-P140 prethalamic histogenetic subdivisions and corresponding nuclear derivatives, in the context of local tract landmarks. The study used as fundamental material brains from a transgenic mouse line that expresses LacZ under the control of an intragenic enhancer of Dlx5 and Dlx6 (Dlx5/6-LacZ). Subtle shadings of LacZ signal, jointly with pan-DLX immunoreaction, and several other ancillary protein or RNA markers, including Calb2 and Nkx2.2 ISH (for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
82
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 30 publications
(87 citation statements)
references
References 245 publications
(734 reference statements)
5
82
0
Order By: Relevance
“…1 c, e, i), two positive groups of neurons in the caudal portion of the zona incerta (arrowhead in Fig. 1 g, i; Puelles et al 2020 ) and scattered positive cells in the periventricular mes-diencephalic basal plate (arrow on Fig. 1 e) draw our attention.…”
Section: Resultsmentioning
confidence: 78%
“…1 c, e, i), two positive groups of neurons in the caudal portion of the zona incerta (arrowhead in Fig. 1 g, i; Puelles et al 2020 ) and scattered positive cells in the periventricular mes-diencephalic basal plate (arrow on Fig. 1 e) draw our attention.…”
Section: Resultsmentioning
confidence: 78%
“…The prosomeric forebrain alar-basal longitudinal boundary roughly overlaps the longitudinal lineal expression of Nkx2.2 along the entire forebrain, now including the midbrain ( Figure 1C ; Shimamura et al, 1995 ; Rubenstein et al, 1998 ; Hauptmann et al, 2002 ; Domínguez et al, 2011 ; Puelles et al, 2012 , 2020 ; Nieuwenhuys and Puelles, 2016 ). The Nkx2.2 -positive band extends along the alar-basal boundary (a sign of equilibrium between ongoing floor-caused basal ventralization vs. roof-caused alar dorsalization, a fundamental patterning antagonism) before it can be detected by any other means.…”
Section: The Hypothalamus In a Historic Perspective: The Columnar Modmentioning
confidence: 84%
“…Expression of Plagl1 , Erbb4 , and Irx1 in the basal peduncular hypothalamus also stops caudally at the Di-Hy boundary. Moreover, the expression of members of the Dlx gene family in the prethalamus (alar rostral diencephalon) partially stops at the molecular hypothalamo-diencephalic boundary (Puelles et al, 2020 ).…”
Section: The Hypothalamus In the Updated Prosomeric Modelmentioning
confidence: 99%
“…A recent research reported that cells in a thin superficial portion of the thalamus switched to GABAergic identity in Tcf7l2 -/embryos, shown by the colocalisation of Gad1 and Gbx2-driven tdTomato signal (Tran et al, 2020). However, the staining resolution does not allow concluding that the signals colocalised in the same cells; and according to the most recent research the origin of thalamic GABAergic cells may be assigned to prethalamic, rostral thalamic and even pretectal domains (Jager et al, 2016;Puelles et al, 2020). More importantly, normal pattern of Vglut2 and Gad1 expression in mice with the postnatally induced knockout of Tcf7l2 demonstrates that TCF7L2…”
Section: Development • Accepted Manuscriptmentioning
confidence: 99%